Ocena przepływu naczyniowego krwi w zwyrodnieniu barwnikowym siatkówki - Steuer, Ewa; Formińska-Kapuścik, Maria; Kamińska-Olechnowicz, Bożena; Kinasz, Renata; Domańska, Olga (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Degeneratio pigmentosa retinae (RP) is one of the most common inherited retinal disease. The authors analyzed the blood flow in the central retinal artery using the DRG Retina Doppler. The blood flow velocity depending on the perimetry was also measured. The outcome of our study was compared to the results obtained from the control group of healthy patients. The comparison showed statistically significant decrease in blood flow velocity in RP patients: Vmax, Vmin, Vaverage. The parameters: resistance index (RI), pulsation rate (PI) did not differ from normal values. Although we observed that the blood flow in RP was decreased even in the case of normal perimetry. The worse the perimetry was, the more reduced was the blood flow. Conclusion: measurements of blood flow may be of use in monitoring the progression of the disease as well as the effects of therapy.